Effects of Zinc Source and Level in Low ABC-4 Diets on Nursery Pig Growth Performance and Fecal Characteristics - Jonathan Riedmüller; Jamil E. G. Faccin; Alessandra R. Monteiro; Jürgen Zentek; Joel M. DeRouchey; Jordan T. Gebhardt; Robert D. Goodband; Jason C. Woodworth; Mike D. Tokach (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 360 weanling barrows (DNA 200 × 400; initially 13.0 ± 0.07 lb) were used in a 38-d study to evaluate the effects of diets containing different levels of a novel Zn source (HiZox, Animine Precision Minerals, Annecy, France) and different levels of crude protein (CP) in low acid-binding capacity at pH 4 (ABC-4) diets on growth performance and fecal characteristics. Pigs were randomly assigned to pens (5 pigs per pen) and pens were assigned to 1 of 6 treatments with 12 pens per treatment. Diets were fed in 3 phases: phase 1 from d 0 to 10, phase 2 from d 11 to 24, and phase 3 from d 25 to 38. All diets were formulated to have low ABC-4. Treatment 1, the negative control (NC), was formulated to contain 150 ppm of Zn (HiZox) throughout the experiment (d 0 to 38). Treatment 2, the positive control (PC), was formulated to contain 3,000 ppm (phase 1) and 2,000 ppm (phase 2) of Zn (ZnO). Treatment 3 (low HiZox) contained 500 ppm (phase 1) and 300 ppm (phase 2) of Zn. Treatment 4 (low HiZox + low CP) was formulated similar to treatment 3 but contained lower CP (19.3% CP) than the NC, PC, low, and high HiZox treatments (21.3% CP). Treatment 5 (high HiZox) contained 800 ppm (phase 1) and 500 ppm (phase 2) of Zn. Treatment 6 (high HiZox + low CP) was formulated to be similar to treatment 5 but contained less CP (19.3% CP). In phase 3, all pigs were fed a common diet containing 150 ppm of Zn (HiZox) and 21.3% CP. For the experimental period (d 0 to 24), pigs fed high HiZox + low CP had poorer F/G (P<0.05) than NC, PC, low HiZox, and high HiZox. In addition, ADG (quadratic,P= 0.007) and ADFI (quadratic,P= 0.018) increased as HiZox increased, and pigs fed diets with low CP were less feed efficient (P= 0.043) than those fed the same levels of HiZox but with high CP. Overall, pigs fed low CP diets had poorer F/G (P= 0.041) than pigs fed similar levels of HiZox with high CP. For fecal characteristics, pigs fed low CP had higher (P= 0.008) dry matter (DM) and an interaction between day and CP (P= 0.040) was detected for fecal scores with low CP diets improving stool consistency to a greater extent on d 10 than on d 23. In summary, increasing levels of HiZox improved performance of nursery pigs during phases 1 and 2, and pigs fed a regimen of 800 and 500 ppm of HiZox in the first 2 phases in low ABC-4 diets had similar performance to pigs fed pharmacological levels of Zn from ZnO in the overall period. Finally, pigs fed low CP diets had improved fecal characteristics, but poorer F/G throughout the nursery period.
Keywords: ABC-4; crude protein; nursery; swine; zinc oxide